PANCAP and the Caribbean development agenda for 2015 and beyond : the struggle to defeat AIDS continues - Greene, Edward (2013)
Posits that PANCAP should use the process of preparing its Caribbean Regional Strategic Plan (CRSF) 2014-18 to focus on the challenges and opportunities for bringing an end to the AIDS epidemic.